Water Rehydration blunted Vasopressin, Angiotensin II and HSP70 responses to High Environmental Temperature without altering Plasma Osmolality in male Sprague-Dawleys rats (African Journal of Biomedical Research, 2020)
factor. HET alters body fluid balance and elevates plasma osmolality, with consequent release of angiotensin II and arginine vasopressin (AVP) , implicated in the pathophysiology of some forms of hypertension. This study investigated the effect of water rehydration on plasma osmolality, angiotensin II, arginine AVP and heat shock protein (HSP70) during chronic exposure to HET. Eighteen (18) male Sprague-Dawley rats (n = 6/group, 8 weeks old, weight: 90-100g) were either kept in an environmental chamber maintained at a HET (38.5±0.5oC ) 4hrs daily without (H) or with access to water (RH) compared to control rats (C), maintained at room temperature of 25 ±0.5oC oC. Experiment lasted 8 weeks. There was a significant increase in plasma osmolality (P